Pengelolaan Daerah Aliran Sungai Berbasis Good Environmental Governance (Jurnal Bina Praja, 2022)
This study aims to analyze the Management of the Batang Arau River Basin in Padang City with a Good Environmental Governance approach, as well as the Government's efforts to overcome obstacles in managing the Batang Arau watershed. This research is a qualitative type with data analysis techniques Manual Data Analysis Procedure (MDAP). The results showed that Batang Arau Watershed Management has not been implemented following the Good Environmental Governance Principles, according to the coding results, namely #1 Low public awareness, #2 Environmental protection laws are not optimal, #3 Unopened access to information on industrial waste, #4 The government's responsiveness is quite good, #5 Environmental consensus has not been reached, #6 occurs ego-sectoral, #7 Long bureaucratic path, #8 No implementation of environmental responsibility. #9 Obstacles, unified vision of management between stakeholders, insufficient budget and fleet, low supervision, there is no integrated IPAL facility, Illegal logging still occurs in upstream watersheds, and coordination between sectors is still problematic. #10 Efforts made by the government are; Providing socialization and education to the community, cleaning and dredging the Batang Arau watershed, normalizing the Batang Arau watershed, and rehabilitating critical watershed areas. The management of the Batang Arau watershed must be carried out thoroughly so that there is no gap between upstream and downstream. To create a balanced ecosystem, the Government needs to reform the watershed management with a Good Environmental Governance approach in every action in the formulation, planning, and implementation of the Batang Arau watershed program to create sustainable management.